2014
DOI: 10.3390/jcm3030849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cell-Free Fetal DNA Screening on Patients’ Choice of Invasive Procedures after a Positive California Prenatal Screen Result

Abstract: Until recently, maternal serum analyte levels paired with sonographic fetal nuchal translucency measurement was the most accurate prenatal screen available for Trisomies 18 and 21, (91% and 94% detection and false positive rates of 0.31% and 4.5% respectively). Women with positive California Prenatal Screening Program (CPSP) results have the option of diagnostic testing to determine definitively if the fetus has a chromosomal abnormality. Cell-free fetal (cff-) DNA screening for Trisomies 13, 18, and 21 was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Twenty-one manuscripts met the inclusion criteria for part A, reporting on 27 countries, states or autonomous regions in Europe, North America and Asia that implemented NIPT as part of a recommended antenatal screening policy for DS between 2011 and 2023 (Fig 2). Eight were retrospective cohort studies of population-based data [11,13,15,20,21,[26][27][28], evaluating the implementation of NIPT into their screening programmes for DS, and four were prospective cohort studies [14,[29][30][31]. Also included were eight official government documents describing the implementation of NIPT [12,[32][33][34][35][36][37][38] and one study that undertook a survey of clinical experts worldwide, providing data on multiple countries [16].…”
Section: Part A-the Implementation and Uptake Of Nipt In National Ant...mentioning
confidence: 99%
“…Twenty-one manuscripts met the inclusion criteria for part A, reporting on 27 countries, states or autonomous regions in Europe, North America and Asia that implemented NIPT as part of a recommended antenatal screening policy for DS between 2011 and 2023 (Fig 2). Eight were retrospective cohort studies of population-based data [11,13,15,20,21,[26][27][28], evaluating the implementation of NIPT into their screening programmes for DS, and four were prospective cohort studies [14,[29][30][31]. Also included were eight official government documents describing the implementation of NIPT [12,[32][33][34][35][36][37][38] and one study that undertook a survey of clinical experts worldwide, providing data on multiple countries [16].…”
Section: Part A-the Implementation and Uptake Of Nipt In National Ant...mentioning
confidence: 99%
“…In conventional screening practice, not all women with a screen‐positive result undergo invasive prenatal diagnosis, and there is evidence that if a secondary cfDNA protocol is adopted, the number of women having neither cfDNA nor invasive prenatal diagnosis will be decreased. Four out of the five studies of women with screen‐positive result comparing uptake before and after initiating the study found such a decrease, even though cfDNA testing was not free of charge. Assuming a decrease from 20% in conventional screening to 10% in a secondary cfDNA protocol, if the proportion presenting late was 15%, the combined test/quad test conventional protocol would cost €533 000 and the secondary cfDNA/primary cfDNA protocol would cost €550 000.…”
Section: Model‐predicted Proportion Of Down‐syndrome Cases Detected Amentioning
confidence: 99%
“…Tables 1 and 2 make the simplifying assumption of complete uptake of screening, invasive prenatal diagnosis and cfDNA testing. Seven studies have been published in which women with positive Down-syndrome screening results were offered the choice between invasive prenatal diagnosis and cfDNA testing [17][18][19][20][21][22][23] . These show no consistent overwhelming preference for one or the other test.…”
Section: Assumptions About Uptakementioning
confidence: 99%
See 1 more Smart Citation